Isolation and preliminary study the scorpion neurotoxins Buthus sp - Anh, Hoang Ngoc; V. E., Piskorev; B. B., Berezin; I. A., Yamskov (Academia Journal of Biology, 2015)
Isolation and preliminary study the scorpion neurotoxins Buthus sp